SAT0379 SUBCUTANEOUS VERSUS ORAL METHOTREXATE IN ACHIEVING MINIMAL DISEASE ACTIVITY IN PSORIATIC ARTHRITIS. CLINICAL PRACTICE: RUSSIAN PSORIATIC ARTHRITIS REGISTRY (RU-PSART) DATA. (June 2019) - Gubar, Elena; Loginova, Elena; Koltakova, Anastasia; Korsakova, Yulia; Korotaeva, Tatiana; Nasonov, Evgeny; Lila, Alexander; Sedunova, Maria; Pristavsky, Igor; Umnova, Irina; Bondareva, Irina; Kudishina, Snezana
Abstract : Background: The aim of psoriatic arthritis (PsA) therapy is to achieve minimal disease activity (MDA) or clinical remission. Methotrexate (MTX) is the first-line treatment; however, the extent of the disease-modifying effect of MTX on PsA is a matter of debate. It has been shown that the MTX treatment achieves MDA in 6 months in <20% of patients (pts) (1). It has been demonstrated that parenterally administered MTX results in rapid and complete absorption, higher serum levels, and less variable exposure than the oral dosing (2). Clinical practice data on the results of the use of MTX for treating PsA are contradictory. Objectives: To show the efficacy of MTX in PsA pts in clinical practice and to compare the effectiveness of oral and subcutaneous (SC) MTX treatments. Methods: 256 pts out of RU-PsART received synthetic disease-modifying antirheumatic drugs (sDMARDs), of whom 182 (71.1%) pts (M/F–68/114) received MTX, and were included in the study according to CASPAR criteria. Their median age 42 [Min 19-Max 73] years (yrs). Pts underwent standard clinical examination of PsA activity at the baseline and the follow-up visits. All pts were biological-naïve. They all were treated with MTX monotherapy: 80 received SC and 102 oral MTX. The main purpose was to determine the cumulative frequency of achieving MDA after the MTX therapy onset. MDA is defined as: the presence of at least 5 out of the following 7 domains: tender joint count ≤1, swollen joint count (SJC) ≤1, Psoriasis Area Severity Index (PASI) ≤1 or body surface area ≤3%, tender entheseal points ≤1, Health Assessment Questionnaire score ≤0.5, patient global disease activity measured by Visual Analogue Scale (VAS) score ≤20, and patient pain VAS ≤15. Medians and quartiles [Me (Q25; Q75)], [Min; Max], ORs with 95% CI, Breslow, Long Rank, Tarone-Ware tests were performed. Cumulative frequency was computed using the Kaplan-Meier method. All CI >1, p <0.05 were considered to indicate statistical significance. Results: Only 16.5% of all 182 pts treated with MTX, both orally and SC, achieved MDA. In the SC MTX group 25 pts (31%) achieved MDA, while 55 (69%) did not achieve it. In the oral MTX group 5 pts (5%) achieved MDA, while 97 (95%) did not achieve it. SC MTX treated pts significantly more often achieved MDA compared with those orally treated OR 8.8 [3.2 – 24.3]. Cumulative frequency of achieving MDA in 27 months from the treatment onset was 48% for SC administration, and 7% for the oral one (p<0.05). MTX median dose in SC administered pts who achieved MDA was 17 mg/weekly (wk), and 15 mg/wk in the group of pts who did not achieve MDA. Among orally administered pts who both achieved and did not achieve MDA the MTX dose was 15 mg/wk. Conclusion: In clinical practice, the sDMARD given to the majority of pts is MTX, but its use achieves the recommended treatment target of MDA only in 16.5% of pts. The SC MTX treatment significantly, up to 30%, improves the achievement of MDA. The use of SC MTX could be a therapy optimized option in clinical practice. References: [1] B.J. Sheane, et al. J Rheumatol. 2016;43(9):1718-23. [2] G.A. Vena et el. Ther Clin Risk Manag. 2018;14:105-16. Disclosure of Interests: ELENA GUBAR: None declared, Elena Loginova Speakers bureau: Novartis, Celgene Corporation, Biocad, Janssen, AbbVie Inc, Anastasia Koltakova: None declared, Yulia Korsakova Speakers bureau: Celgene Corporation, Janssen, Tatiana Korotaeva Consultant for: Pfizer, MSD, Novartis, AbbVie, Celgene, Biocad, Janssen, UCB, Lilly and Novartis-Sandoz, Speakers bureau: Pfizer, MSD, Novartis, AbbVie, Celgene, Biocad, Janssen, UCB, Lilly and Novartis-Sandoz, Evgeny Nasonov Speakers bureau: Pfizer, Inc., MSD, Novartis, AbbVie Inc., Celgen Corporation, Biocad, Janssen, UCB, Inc., Alexander Lila Speakers bureau: Pfizer, Inc., MSD, Novartis, AbbVie Inc., Celgen Corporation, Biocad, Janssen, UCB, Inc., Maria Sedunova: None declared, Igor Pristavsky: None declared, Irina Umnova: None declared, Irina Bondareva: None declared, Snezana Kudishina: None declared